Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3847/1538-4357/ab09f2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Current Piston for Generating Extreme-ultraviolet Fronts in the Solar Corona

Abstract: Single-pulse, globally propagating coronal fronts, called Extreme-ultraviolet (EUV) waves, were first observed in 1995 by the Extreme-ultraviolet Imaging Telescope and every observed EUV wave since has been associated with a coronal mass ejection (CME). The physical mechanism underlying these waves has been debated for two decades with wave or pseudo-wave theories being advocated. We propose a hybrid model where EUV waves are compressional fronts driven by a reverse electric current layer induced by the time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Wongwaitayakornkul et al. (2019) have shown that this piston motion can drive a shock wave in the background plasma and have proposed this CME‐driven shock as an explanation for the EUV waves (Long et al., 2017) that are often seen in association with CMEs.…”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wongwaitayakornkul et al. (2019) have shown that this piston motion can drive a shock wave in the background plasma and have proposed this CME‐driven shock as an explanation for the EUV waves (Long et al., 2017) that are often seen in association with CMEs.…”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 99%
“…These models are not only relevant to solar physics, but also to magnetospheric physics and to astrophysics which can have similar physics but at very different scales from the lab or the Sun. Examples of such theoretical models are the following: A model showing why flux ropes tend to be collimated (Bellan, 2003) A model for how accretion disks and astrophysical jets form a complete electric circuit that transfers angular momentum in a conservative way much like a generator transfers angular momentum via wires to a distant motor (Bellan, 2016a, 2018d) A model providing a time‐dependent analytic solution for an astrophysical jet (Bellan, 2020) A model for how energetic particles are created in the presence of sub‐Dreicer electric fields (Marshall & Bellan, 2019) A model providing an intuitive explanation for fast collisionless magnetic reconnection (Yoon & Bellan, 2017, 2019a) in the electron MHD context, that is, the context where the timescale is so fast that ions can be considered stationary, and the reconnection length scale is short compared to the ion skin depth, so Hall terms and electron inertia are important. A model showing that ions experience fast stochastic heating during fast collisionless reconnection (Yoon & Bellan, 2018, 2019b) A model showing how the reverse current associated with coronal mass ejection drives EUV fronts in the solar corona (Wongwaitayakornkul et al., 2019) …”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 99%